Redox homeostasis in sport: do athletes really need antioxidant support?. Issue 2 (3rd April 2019) - Antonioni, Ambra; Fantini, Cristina; Dimauro, Ivan; Caporossi, Daniela
ABSTRACT: Supplementation with antioxidants received interest as suitable tool for preventing or reducing exercise-related oxidative stress possibly leading to improvement of sport performance in athletes. To date, it is difficult to reach a conclusion on the relevance of antioxidants supplementation in athletes and/or well-trained people. The general picture that emerges from the available data indicates that antioxidants requirement can be covered by dosage equal or close to the recommended dietary allowance (RDA) provided by consumption of a balanced, well-diversified diet. Nevertheless, it remains open the possibility that in specific context, such as in sports characterized by high intensity and/or exhaustive regimes, supplementation with antioxidants could be appropriated to avoid or reduce the damaging effect of these type of exercise. This review will discuss the findings of a number of key studies on the advantages and/or disadvantages for athletes of using antioxidants supplementation, either individually or in combination.